Thermodynamic evaluation and optimization of a flat plate collector operating with alumina and iron mono and hybrid nanofluids. (February 2020) - Okonkwo, Eric C.; Wole-Osho, Ifeoluwa; Kavaz, Doga; Abid, Muhammad; Al-Ansari, Tareq
Abstract: This study presents a thermodynamic evaluation of a flat plate collector (FPC) operating with both mono and hybrid nanofluids. The performance of a collector operating with alumina-water, alumina-iron/water hybrid nanofluids, and water as its heat transfer fluids are evaluated. The two nanofluids were experimentally synthesized at nanoparticle concentrations of 0.05%, 0.1%, and 0.2%, their thermal properties were measured for varying temperature ranges and is used to create a correlation model for the thermal conductivity, specific heat, and viscosity of the nanofluids. A thermal model for the FPC was created on the engineering equation solver for both the first law and second law evaluation of the collector. Then a parametric study and optimization of the system were carried out for varying values of temperature, nanoparticle volumetric fraction and mass flow rate. The results show that the use of alumina-water at a concentration of 0.1% presented a thermal enhancement of 2.16% in the collector, while the hybrid nanofluids reduced the thermal performance of the collector by 1.79% when compared to water. Though the use of the hybrid nanofluids did not provide a better thermal option to water, it provided an exergetic efficiency enhancement of 6.9% as against 5.7% using the alumina-water nanofluids.